2004
DOI: 10.1124/mol.104.002410
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mechanisms Are Involved in Ah Receptor-Mediated Cell Cycle Arrest

Abstract: The liver is the only solid organ that can respond to major tissue loss or damage by regeneration to restore liver biomass. The aryl hydrocarbon receptor (AhR) agonist 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) can disrupt the regenerative process, as evidenced by suppression of DNA synthesis in rat primary hepatocytes in culture and in vivo liver regeneration after partial hepatectomy. Independent observations demonstrated that AhR-mediated G 1 phase cell cycle arrest depends on an interaction with the retino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 48 publications
5
68
0
Order By: Relevance
“…Recent data from our laboratory [Marlowe et al, 2004] and from Elferink and colleagues [Huang and Elferink, 2005] have confirmed this conclusion. AHR activation in cycling Hepa-1c1c7 cells results in the accumulation of cells in G 1 [Marlowe et al, 2004].…”
Section: Cell Cycle Arrest Induced By Ahr Ligandssupporting
confidence: 73%
“…Recent data from our laboratory [Marlowe et al, 2004] and from Elferink and colleagues [Huang and Elferink, 2005] have confirmed this conclusion. AHR activation in cycling Hepa-1c1c7 cells results in the accumulation of cells in G 1 [Marlowe et al, 2004].…”
Section: Cell Cycle Arrest Induced By Ahr Ligandssupporting
confidence: 73%
“…Treatment of mouse hepatoma cells with a component of tobacco smoke [2,3,7,8-tetrachlorodibenzo- Daily use of supplements containing folic acid (400-500 g) from 4 weeks before conception of the child until 8 weeks after; incidental users and women who started folic acid supplements later than 4 weeks before conception were excluded c Any folic acid use during pregnancy, also incidental users and women who started folic acid supplements later than 4 weeks before conception were included resulted in the co-repression of E2F-mediated expression of genes necessary for cell cycle progression (Huang and Elferink 2005). Another interesting hypothesis is that AhR suppresses Tgfb3 expression and Tgfb3 has an indirect eVect on IRF6.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is the only solid organ known to be capable of regenerating organ mass in response to damage (Huang and Elferink, 2005). This is important given the role of the liver in metabolism of both endogenous and exogenous compounds.…”
Section: Introductionmentioning
confidence: 99%